2017
DOI: 10.1021/acs.inorgchem.7b00636
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Evidences of p-Type Conductivity in Nickel Carbodiimide Nanoparticles with a Delafossite Structure Type

Abstract: Nickel carbodiimide (NiCN) was synthesized using a two-step precipitation-decomposition route leading to a brown powder with gypsum-flower-like morphology and a large specific surface area (75 m/g). This layered material crystallizes in the 2H structure type of delafossite (space group P6/mmc), which is built upon infinite /[NiN] layers connected by linear carbodiimide ([N═C═N]) bridges. An X-ray diffraction Rietveld refinement and thermal analyses pointed out some nickel deficiencies in the material, and band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
3
11
0
Order By: Relevance
“…The scanning electronic microscopy (SEM) image, shown in Figure b, reveals an intergrowth of flakes that look like desert rose petals with a size of several micrometers. As reported for other transition‐metal carbodiimide materials, Cr 2 (NCN) 3 also undergoes a minor initial weight loss (≈1.1%) in the 0–350 °C range followed by an abrupt loss (≈28%) at 400 °C, as shown from the thermogravimetric analysis (TGA) yellow plot in Figure b. The initial loss is mainly due to the departure of adsorbed water from the surface of the sample, whereas the second one corresponds to the decomposition into chromium oxide .…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The scanning electronic microscopy (SEM) image, shown in Figure b, reveals an intergrowth of flakes that look like desert rose petals with a size of several micrometers. As reported for other transition‐metal carbodiimide materials, Cr 2 (NCN) 3 also undergoes a minor initial weight loss (≈1.1%) in the 0–350 °C range followed by an abrupt loss (≈28%) at 400 °C, as shown from the thermogravimetric analysis (TGA) yellow plot in Figure b. The initial loss is mainly due to the departure of adsorbed water from the surface of the sample, whereas the second one corresponds to the decomposition into chromium oxide .…”
Section: Resultssupporting
confidence: 64%
“…As reported for other transition‐metal carbodiimide materials, Cr 2 (NCN) 3 also undergoes a minor initial weight loss (≈1.1%) in the 0–350 °C range followed by an abrupt loss (≈28%) at 400 °C, as shown from the thermogravimetric analysis (TGA) yellow plot in Figure b. The initial loss is mainly due to the departure of adsorbed water from the surface of the sample, whereas the second one corresponds to the decomposition into chromium oxide . The final weight loss step from 500 to 700 °C can be attributed to the decomposition to form nanocrystalline chromium oxide as seen in the normal transition‐metal oxides …”
Section: Resultssupporting
confidence: 56%
“…The initial loss is associated with water or organic molecules desorption from the particles’ surface. The second abrupt loss is due to the decomposition of cobalt carbodiimide into cobalt oxide …”
Section: Resultsmentioning
confidence: 99%
“…The good number of available properties of both polytypes of delafossite oxides suggests a strong structure–property relation in them. Jiang et al have recently studied the NiCN 2 compound in delafossite structure and found p‐type conductivity in this compound. Tiago et al predicted several Cu, Ag, and Au‐based ternary oxides in delafossite structures.…”
Section: Introductionmentioning
confidence: 99%